Rare presentation of neurofibromatosis and Turner syndrome in a pediatric patient - Natalie Gengel; Ian Marshall (MDPI AG, 2017)
Neurofibromatosis type 1 (NF1) is classically defined by the presence of multiple café-au-lait macules as one of the diagnostic criteria. Turner syndrome (TS) can also present with café-au-lait macules along with short stature. Our patient is the fifth reported with both NF1 and TS and the first who has been on growth hormone for short stature associated with TS.